Hepatitis C Virus RNA Replication and Virus Particle Assembly Require Specific Dimerization of the NS4A Protein Transmembrane Domain - Kohlway, Andrew (American Society for Microbiology, 2014)
Hepatitis C virus (HCV) NS4A is a single-pass transmembrane (TM) protein essential for viral replication and particle assembly. The sequence of the NS4A TM domain is highly conserved, suggesting that it may be important for protein-protein interactions. To test this hypothesis, we measured the potential dimerization of the NS4A TM domain in a well-characterized two-hybrid TM protein interaction system. The NS4A TM domain exhibited a strong homotypic interaction that was comparable in affinity to glycophorin A, a well-studied human blood group antigen that forms TM homodimers. Several mutations predicted to cluster on a common surface of the NS4A TM helix caused significant reductions in dimerization, suggesting that these residues form an interface for NS4A dimerization. Mutations in the NS4A TM domain were further examined in the JFH-1 genotype 2a replicon system; importantly, all mutations that destabilized NS4A dimers also caused defects in RNA replication and/or virus assembly. Computational modeling of NS4A TM interactions suggests a right-handed dimeric interaction of helices with an interface that is consistent with the mutational effects. Furthermore, defects in NS4A oligomerization and virus particle assembly of two mutants were rescued by NS4A A15S, a TM mutation recently identified through forward genetics as a cell culture-adaptive mutation. Together, these data provide the first example of a functionally important TM dimer interface within an HCV nonstructural protein and reveal a fundamental role of the NS4A TM domain in coordinating HCV RNA replication and virus particle assembly.